2022
DOI: 10.1212/nxi.0000000000001159
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Retinal Vessel Loss After Acute Optic Neuritis in Patients With Relapsing Multiple Sclerosis

Abstract: Background and ObjectivesRarefication of the retinal vasculature as measured by optical coherence tomography angiography (OCT-A) is a novel finding in patients with multiple sclerosis (MS). This study aimed to analyze longitudinal dynamics of the retinal vasculature following an acute inflammatory relapse including acute optic neuritis (ON) and to search for associations with alterations of the retinal architecture and visual function.MethodsThis prospective longitudinal cohort study included patients with rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…and was manually corrected if necessary. OCT-A examinations were acquired on both eyes of each patient under low-lighting conditions using a spectral-domain OCT with angiography module (Heidelberg Engineering Spectralis OCT2) by two experienced technicians as previously described (6). En face images and decorrelation signals were recorded within a 2.9 × 2.9 mm area focusing on the fovea centralis with active eye tracking algorithm.…”
Section: Oct and Oct-a Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…and was manually corrected if necessary. OCT-A examinations were acquired on both eyes of each patient under low-lighting conditions using a spectral-domain OCT with angiography module (Heidelberg Engineering Spectralis OCT2) by two experienced technicians as previously described (6). En face images and decorrelation signals were recorded within a 2.9 × 2.9 mm area focusing on the fovea centralis with active eye tracking algorithm.…”
Section: Oct and Oct-a Analysismentioning
confidence: 99%
“…There is growing evidence that patients suffering from autoimmune diseases of the central nervous system also reveal alterations of the retinal vasculature. We could recently show that an acute optic neuritis (ON) leads to loss of retinal vessels within the superficial vascular complex (SVC) during the first 90 days after ON (6). Superficial vessel loss might also occur in eyes without a history of ON and might be linked to a worse visual function and disability (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies focused on the changes in the FAZ area in MS ( 15 17 ) showing ambiguous results, probably due to differences in OCTA devices ( 32 34 ). Only one study, conducted by Hayati et al, reported a significant correlation only between the FAZ area and the inner rings of SCP, analyzing a 3 × 3mm macula area ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, using OCTA, found a significant impairment of retinal blood flow focusing on limited retinal fields, namely the macular region or the foveal avascular zone (FAZ) (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…One recent study failed to find any significant differences in SVP VD between pwMS and controls but showed discrepancies between the two groups in the RNFL, GC-IPL, and radial peripapillary capillary (pRPC) VD [ 51 ]. Thinning of the SVP and enlargement of the FAZ appear to progress rapidly after an episode of ON and are associated with a persistent visual disability [ 52 ].…”
Section: Optical Coherence Tomography With Angiography In Multiple Sc...mentioning
confidence: 99%